Draft Dictionary of Synonymic-Antonymic Complexes: Problems of Lexicographic Interpretation of Typical Semantics and Ways to Solve Them - L. G. Babenko (Научный диалог, 2019)
The new lexicographic project of the Ural semantic school, the Large Ideographic Dictionary of Synonymic-Antonymic Complexes, the concept of which is generally developed and is currently being implemented in the process of writing dictionary articles, is highlighted. It is noted that in Russian lexicography there are no comprehensive dictionaries based on the integrative consideration of synonyms and antonyms in their unity, which determines the relevance of creating new lexicographic sources. For the first time, a fundamentally new lexical set was chosen as the object of lexicographic description - a synonymic-antonymic complex, which has a unique structural-semantic organization based on the integration of units connected simultaneously by relations of opposites (antonyms) and identities (synonyms). The principal novelty of the project also lies in the fact that it provides an ideographic description of synonymic-antonymic complexes, which are distributed in the global structure of the dictionary, taking into account their general type semantics, by spheres, fields, classes, groups and subgroups. The author pays special attention to the problem of lexicographic interpretation of the integral type semantics of the entire synonymic-antonymic complex, as well as the type semantics of its main subgroups and the individual semantics of private antonymic oppositions. The solutions to this problem are given.